2009
DOI: 10.1016/j.vaccine.2009.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Development and use of SIV-based Integrase defective lentiviral vector for immunization

Abstract: Integrase (IN) defective lentiviral vectors have a high safety profile and might prove useful as immunizing agents especially against HIV-1. However, IN defective SIV-based vectors must be developed in order to test their potential in the non human primate models (NHP) of AIDS. To this aim we tested a novel SIV-based IN defective lentiviral vector for its ability to induce sustained immune responses in mice. BALB/c mice were immunized once intramuscularly with a SIV-based IN defective lentiviral vector express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 41 publications
6
64
0
Order By: Relevance
“…A non-integrating SIV vector has been described recently. 87 Clinical trials for eAMD and Stargardt macular dystrophy using non-primate lentiviral vectors Considerable progresses in lentiviral vector development and promising pre-clinical efficacy and safety profiles have permitted the initiation of the first ocular clinical trials using lentiviral vectors. Retinostat is a bicistronic EIAV vector delivering both endostatin and angiostatin under the control of the RPE-specific VMD2 promoter, and has shown favourable pre-clinical efficacy and safety profiles.…”
Section: Posterior Segment Applicationsmentioning
confidence: 99%
“…A non-integrating SIV vector has been described recently. 87 Clinical trials for eAMD and Stargardt macular dystrophy using non-primate lentiviral vectors Considerable progresses in lentiviral vector development and promising pre-clinical efficacy and safety profiles have permitted the initiation of the first ocular clinical trials using lentiviral vectors. Retinostat is a bicistronic EIAV vector delivering both endostatin and angiostatin under the control of the RPE-specific VMD2 promoter, and has shown favourable pre-clinical efficacy and safety profiles.…”
Section: Posterior Segment Applicationsmentioning
confidence: 99%
“…We previously demonstrated that a single intramuscular injection of IDLV induced systemic antigen-specific CD8+ T cell responses that were detectable up to 3 months in spleen, draining LN and bone marrow derived cells [23], [25], [39]. Here we showed for the first time that antigen-specific CD8+ T cells induced after a single i.m.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, we demonstrated that a single immunization with an IDLV expressing the HIV-1 envelope protein in the mouse immunogenicity model was able to elicit strong and longlasting specific immune responses in the absence of vector integration, thus providing safe and efficient delivery for vaccine purposes (Negri et al, 2007). Importantly, several groups confirmed the use of IDLVs as an effective vaccine delivery strategy (Coutant et al, 2008;Hu et al, 2009;Karwacz et al, 2009), and we provided evidence that SIV-based IDLVs can be constructed and used as well (Michelini et al, 2009).…”
mentioning
confidence: 63%
“…Gene transfer to APCs has several advantages over pulsing with protein or peptide, such as the possibility of presentation of multiple epitopes for a functional cytotoxic T lymphocyte (CTL) response, a continuous supply of antigen for sustained presentation, and the coexpression of cytokine genes along with the antigen of interest. We and others have already demonstrated that IDLVs are able to transduce both murine and human APCs (Gillim-Ross et al, 2005;Coutant et al, 2008;Berger et al, 2009;Michelini et al, 2009), and that integrase (IN) mutants prevent virus integration in transduced macrophages (Cara et al, 1995;Kelly et al, 2008;Zheng et al, 2008). However, a proof-ofconcept study showing that IDLV-transduced human APCs are able to induce the antigen-specific T cell expansion of primed T cells is still lacking.…”
mentioning
confidence: 99%